Sosialisasi Peningkatan Pengetahuan Keamanan Dalam Jual Beli Online - Thomas Afrizal; Han Sulaiman; Dwi Yulistyanti; Naely Farkhatin; Aulia Paramita (CV. ALIM'SPUBLISHING, 2024)
The increasing number of internet users makes Indonesia a very potential market for e-commerce. The growth of the middle class and the literacy rate of online buyers and sellers is also growing. E-commerce itself is not new, but its rise marks a new milestone for this industry in the country. Although it is growing quite rapidly, there is still one major problem that is preventing e-commerce in Indonesia from taking off, namely the problem of consumer trust in e-commerce sites. Consumers still do not trust the sales system with a non-physical buying and selling process, do not trust to provide credit card numbers to e-commerce services and are still afraid of fraud. However, this crisis of trust can actually be solved. One of the many ways is to use a payment service that has guaranteed security. Not all e-commerce can provide their own payment system, now there are many services that provide a secure payment system and are especially easy to apply to online stores. E-commerce players can use this payment system easily, quickly and which can improve the performance process in their online stores. However, the selection of services that provide a payment system must also be considered carefully. A secure payment system provider will provide a sense of security to prospective buyers, meaning that consumer trust must be built by e-commerce service providers so that consumers can be comfortable and do not encounter problems in making purchases and paying for products in the online stores provided.Security is important, the use of credit cards is widely highlighted because there are still many unpleasant incidents or fraud that occur due to the use of credit cards. Education on this security needs to be carried out continuously, because it will be related to consumer behavior.